Analysis of Farmers’ Knowledge and Attitude Towards Lac Cultivation in Bangladesh (Bangladesh Journal of Agricultural Research, 2022)
The study was a descriptive survey, which was undertaken to describe the lac grower’s knowledge and attitude towards lac cultivation. The study was conducted at two lac growing area of Naogan and Chapainawabganj district. Sixty lac farmers were selected randomly from selected area and considered as sample of the study. The interview schedule was developed according to the objective of the study. The farmer’s knowledge on lac cultivation was calculated by answering 10 questions related to lac cultivation. Five point likertscale was employed to judge 15 attitude measuring statements towards lac cultivation. The highest proportion (36.67%) of the respondent was in 50%and above knowledge category but no respondent was found at 80% and above knowledge category. Maximum (86.67%) respondents possessed moderately to highly favourable attitude towards lac cultivation where only13.33% possessed less favourable attitude. Among the socio demographic characteristics, training exposure showed significant positive relationship with farmer’s knowledge and attitude where education showed significant positive relationship with farmer’s knowledge. Different need based lac cultivation related training to farmer can play vital role for development and popularization of lac cultivation.Bangladesh J. Agril. Res. 45(4): 409-417, December 2020